Development of membrane support for levulinic acid extraction using supported liquid membrane process - Vikneswary, Rajendaran (2022)
Levulinic acid (LA) and its valuable derivatives are in growing demand in various applications. Nowadays, LA from biomass gained significant attention due to concerns over fossil fuel depletion, increasing oil price, and environmental problems. However, the primary challenge in biorefinery is the separation of LA from biomass products. This research aimed to develop a new method for separating LA from biomass products using a supported liquid membrane (SLM). In the initial stage of the study, the organic liquid membrane (LM) phase formulation for LA extraction was established and the operating flat sheet SLM (FSSLM) parameters were optimized using a hybrid graphene/ polyethersulfone (PES) flat membrane as the support. Then, the PES membrane supports were modified using various hydrophobic fillers and pore forming agents. The membrane were characterized in terms of morphology, porosity, membrane hydrophobicity, and mechanical strength. The modified dope solution formulation was used for further PES hollow fiber (HF) spinning investigation. In HF spinning, the fabrication parameters such as bore liquid, air gap and relative humidity in the dry-wet spinning technique were investigated. Later, three hollow fiber supported liquid membrane (HFSLM) operating factors such as tri-n-octylamine (TOA), sodium hydroxide (NaOH), and LA were screened using the full-factorial design (FFD) and optimized using face-centered design (CCF). The kinetic study was conducted, and a model was developed. At last, the efficiency of the SLM technique in LA separation from oil palm frond (OPF) biomass solution was tested using optimized HF at the optimal SLM operation conditions. As a result, 89.2% of LA was extracted via FSSLM from 10g/L of LA solution using a LM formulation of 0.3 M TOA in 2-ethyl-1-hexanol with 0.5 M of NaOH as stripping agent at both feed and stripping flowrate of 75 ml/min. The best flat sheet membrane support was fabricated using 0.1 wt.% graphene and polyethylene glycol 200 as filler and pore-forming agents, respectively. It had a hydrophobic surface with a contact angle of 98°, porosity of 87.1% and tensile stress of 1032.9 kPa. Moreover, it resulted in the highest LA extraction of 89.2%. Furthermore, the best fiber with a hydrophobic surface of 94.1°, 77.57% of porosity, and tensile stress of 1524.7 kPa were spun using 60% v/v dimethylacetamide as the bore fluid, an air gap of 6 cm and relative humidity of 86%. It yielded the highest LA extraction of 72.2%. Moreover, the screening using FFD results were used as a center point (0.5 M TOA, 0. 75 M NaOH, and 10 g/L of LA) to optimize the LA extraction in Response Surface Methodology. The optimal conditions were 0.32 M TOA, 0.77 M NaOH, and 10.08 g/L LA using a CCF. The LA extraction yield was increased after the optimization to a value of 74.82%. Based on the kinetic study, the rate-controlling step in this investigation is LA diffusion across the film layer between the feed and organic phases. The LA transport was proven to be a pure diffusion, and the diffusion controls the LA transport. A newly developed diffusion flux model is considered adequate for LA extraction through HFSLM. The developed methods successfully extracted 63.62% of LA and recovered 40.44% of LA from an OPF biomass solution containing 10.05 g/L LA. Based on this study, SLM method can be used to remove inhibitor, LA, from biomass hydrolysate before fermentation and also proved to be an effective method to separate LA from aqueous biomass solution and OPF compared to some other separation processes.